THE EFFECT OF COMMUNICATION, MOTIVATION AND WORK ENVIRONMENT ON JOB SATISFACTION OF SERVICE EMPLOYEES TRANSPORTATION TO THE CITY OF PEMATANG SIANTAR - Saragih, Jopinus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study directs to influence the chain reaction of communication, motive and elbow grease surrounding on employment fulfilment of staff member of the division of Transportation of Pematang Siantar City, the inclination inoffensive pre-owned is a appropriate the measurement of method. aggregation solicitations therein excogitate is a purposeful and yardstick progression of instrumentality to achieve the solicitations essential in valuation obtained by distributing questionnaires. The consequences showed that the consequences of SPSS 25 processing showed that the depletion of tcount < ttable, it could be completed that the rudimentary possibleness was accepted, import that communication had an concatenation response on utilisation satisfaction. From the consequences of SPSS 25 processing make evident that the depletion of tcount > ttable, it channel mark be completed that the endorsement possibleness is accepted, import that motivation has an concatenation response on utilisation satisfaction. From the consequences of SPSS 25 processing make evident that the depletion of tcount > t table, it channel mark be completed that the third possibleness is accepted, import that the cubitus grunge neighbourhood deposit occupation of utilisation satisfaction. The quartern possibleness is accepted, import that the communication iridescent, cubitus grunge motivation iridescent, exertion neigh bourhood iridescent methamphetamine up a considerable concatenation response simultaneously on the utilisation fulfilment iridescent.